2021
DOI: 10.3390/nu13072459
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Sfrp5 and Wnt5a in the Pathogenesis of Obesity: Implications for a Healthy Diet and Lifestyle

Abstract: In recent decades, the prevalence of obesity has risen dramatically worldwide among all age groups. Obesity is characterized by excess fat accumulation and chronic low-grade inflammation. The adipose tissue functions as a metabolically active endocrine organ secreting adipokines. A novel duo of adipokines, the anti-inflammatory secreted frizzled-related protein 5 (Sfrp5) and the proinflammatory wingless type mouse mammary tumor virus (MMTV) integration site family member 5A (Wnt5a), signal via the non-canonica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 87 publications
1
24
0
Order By: Relevance
“…28 Whereas some studies found Wnt5a was increased in obesity, others could not confirm these observations. 29 Consistent with the findings of Gerdes, 25 our study found that Wnt5a serum concentrations not increased in even severe obesity healthy volunteers. The possible reason may be the number of healthy volunteers in control group was small.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…28 Whereas some studies found Wnt5a was increased in obesity, others could not confirm these observations. 29 Consistent with the findings of Gerdes, 25 our study found that Wnt5a serum concentrations not increased in even severe obesity healthy volunteers. The possible reason may be the number of healthy volunteers in control group was small.…”
Section: Discussionsupporting
confidence: 91%
“…We did not detect the expression of the anti-inflammatory secreted frizzled-related protein 5 (SFRP5), a soluble Wnt5a receptor, always secreted by adipocytes from healthy subjects, and together with Wnt5a involved in the occurrence and development of obesity and inflammatory diseases. 29,30…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that the pro-inflammatory adipokine wingless-type mouse mammary tumor virus integration site family member 5A (Wnt5a), together with the anti-inflammatory secreted frizzled-related protein 5 (Sfrp5), which both signal via the non-canonical Wnt pathway, play a key role in the pathogenesis of obesity and its metabolic complications [151,152]. The circulating levels of Wnt5a and its expression in VAT are increased in obesity [152,153], contributing to systemic and local inflammation [154].…”
Section: Wnt5amentioning
confidence: 99%
“…ROS1 [250], WNT2 [251], PHLDA2 [252], WNT5A [253], HSD11B2 [254], CLDN1 [255], CYP24A1 [256], HRG (histidine rich glycoprotein) [257], TLR3 [258], THBS1 [259], TRPC6 [260], SELP (selectin P) [261], CLU (clusterin) [262], CDKN1A [263], ITGB1 [264], HLA-E [265], IL6R [266], TIMP1 [267], SERPINA1 [268], CD74 [269], PANX1 [270], STIM1 [271] and CXCR4 [272] were revealed to be correlated with disease outcome in patients with preeclampsia. Previously reported studies have shown that the expression of LBP (lipopolysaccharide binding protein) [273], MC1R [274], CXCL14 [275], RGN (regucalcin) [276], NPY2R [277], MFAP5 [278], WNT5A [279], EDA (ectodysplasin A) [280], THSD7A [281], NEUROD1 [282], SLIT2 [283], PPARGC1A [219], IGF1 [144], OSR1 [284], TLR3 [285], BMP7 [286], POSTN (periostin) [287], LRP1B [288], THBS1 [289], NOTCH2 [290]. LRP1 [291], CLU (clusterin) [292], SMAD3 [91], TGFB1 [293], APP (amyloid beta precursor protein) [294], ITGB2 [295], IL6R [296], TIMP1 [297], CD47 [298], CD74 [299], RARA (retinoic acid receptor alpha) [300], DOCK2 [301], F13A1 [302], IRF7 [303], STIM1 [304], CXCR4 [305], MGLL (monoglyceride lipase) [306], M6PR [307], USP22 [308] and CASP2 [309] were mainly involved in progression of obesity, but these genes might be novel targets for GDM.…”
Section: Discussionmentioning
confidence: 99%